2006
DOI: 10.1063/1.2221521
|View full text |Cite
|
Sign up to set email alerts
|

Defect states in the high-dielectric-constant gate oxide LaAlO3

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 30 publications
4
63
2
Order By: Relevance
“…HSE further opens up the band gap placing the V 0 level at 2.19 eV below the conduction band edge (it is 1.32 eV in the LDA). Our results differ from that reported in [40] where the defect state is found to be less deep. Discrepancies could arise due to the different supercell size used.…”
Section: Laalocontrasting
confidence: 57%
See 1 more Smart Citation
“…HSE further opens up the band gap placing the V 0 level at 2.19 eV below the conduction band edge (it is 1.32 eV in the LDA). Our results differ from that reported in [40] where the defect state is found to be less deep. Discrepancies could arise due to the different supercell size used.…”
Section: Laalocontrasting
confidence: 57%
“…Discrepancies could arise due to the different supercell size used. Further, the band gap obtained with screened exchange in [40] Since the neutral oxygen vacancy defect in LAO is a deep defect we further check the presence of V -and V --state inside the gap. We do not find any states occurring within the band gap of LAO corresponding to the above charged states.…”
Section: Laalomentioning
confidence: 99%
“…4(b). While the energy of Vö formation in mixed ionic-electronic conductors can often be described by two electrons going from the O 2p band center to E Fermi [6], the energy levels of the Vö defect states localized around the O vacancy in the metallized AO surface are lower in energy than the AO surface states [81]. The energy of the electrons involved in this defect formation is quite similar to the case of the bulk vacancy formation, where two electrons move from the O 2p band to the defect states close to the CBM.…”
Section: A Charge Of Point Defects and (001) Surfacesmentioning
confidence: 99%
“…4(c). Formation of Vö liberates two electrons, and in the bulk system these electrons fill defect states in the gap close to the conduction band minimum (CBM) [81], while in the hole-doped LaAlO 3 symmetric slab these electrons can fill levels near the valence band maximum (VBM), which costs significantly less energy than filling near the CBM. Again, the fact that E seg (Vö) in the center layer of the 15-layer slab does not converge to the bulk (i.e., yield a zero segregation energy) is consistent with the fact that the surface charge screening length is much longer than the thickness of the simulated symmetric slab for LaAlO 3 .…”
Section: A Charge Of Point Defects and (001) Surfacesmentioning
confidence: 99%
“…Several point defects in bulk LAO and O vacancies in LAO (001) film have been studied theoretically [33][34][35][36]. Using density functional theory Zhang et al [35] have recently shown that O vacancy preferably forms at the AlO 2 surface of the LAO overlayer on STO.…”
Section: Introductionmentioning
confidence: 99%